Socio-economic factors & longevity in a cohort of Kerala State, India - Catherine Sauvaget; Kunnambath Ramadas; Jean-Marie Fayette; Gigi Thomas; Somanathan Thara and Rengaswamy Sankaranarayanan (Indian J Med Res, 2011)
Background & objectives: Even though Kerala State is well-known for its egalitarian policies in terms of healthcare, redistributive actions and social reforms, and its health indicators close to those of high- resource countries despite a poor per-capita income, it is not clear whether socio-economic disparities in terms of life expectancy are observed. This study was therefore carried out to study the impact of socio- economic level on life expectancy in individuals living in Kerala. Methods: A cohort of 1,67,331 participants aged 34 years and above in Thiruvananthapuram district, having completed a lifestyle questionnaire at baseline in 1995, was followed up for mortality and cause of death until 2005. Survival estimates were based on the participants’ vital status and death rates were calculated separately for men and women and for several socio-economic factors, stratified by age. Results: At 40 years, men and women were expected to live another 34 and 37 years, respectively. Life expectancy varied across the participants’ different socio-economic categories: those from high income households with good housing conditions, materially privileged households and small households, had a 2-3 years longer life expectancy as compared to the deprived persons. Also, those who went to college lived longer than the illiterates. The gaps between categories were wider in men than in women. Interpretation & conclusions: Socio-economic disparity in longevity was observed: wealthy people from Kerala State presented a longer life expectancy.